Site classification of seismic recording stations of Garhwal region of earthquake early warning system for Uttarakhand, India - Kumar, Pankaj; Pandey, Bhavesh; Kamal; Kumar, Ashok (Vietnam Journal of Earth Sciences, 2022)
Site classification is vital to carry out seismic hazard analysis of a region and get the damage patterns caused by earthquakes. In the present study, the ground motion of earthquakes recorded from 2015 to 2019 at 84 sites of the seismic network array of Earthquake Early Warning System for Uttarakhand are analyzed for site classification purposes. The predominant period from the mean horizontal to vertical spectral ratio curves was estimated. The classification schemes devised by Japan Road Association and National Earthquake Hazards Reduction Program are applied to classify the sites. Along with this, two other site classification indexes schemes are also applied for classification purposes. Data winnowing techniques are used over the ground motion records to pick out desirable quality records. Conclusively, the site class with the highest recurrence rate amongst the used methods is selected as the final class for that particular site. The effect of magnitude, distance and depth on horizontal to vertical spectral ratio are described and concluded that these factors do not significantly affect the ratio curves. The average horizontal to vertical spectral ratio curves obtained for all the sites matches well with the existing literature. The classification of a few sites are verified from the classification done by other methods in recent studies. It is evident from the results that the classification done in this study matches well with them.